Liver Transplantation in Situs Inversus and Portal Vein Thrombosis (First Case Report in Russia) - M. S. Novruzbekov; O. D. Olisov; V. A. Guliaev; K. N. Lutsyk; K. M. Magomedov; B. I. Kazymov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Situs inversus is a rare mirror transposition of internal organs relative to the median plane. Liver transplantation in situs inversus is a serious medical challenge imposed by an abnormal arrangement of the recipient's organs.Aim. Clinical description of a successful cadaveric liver transplantation in an adult patient with situs inversus and portal vein thrombosis.Key points. A 32 years-old patient with situs inversus, chronic hepatitis B/D-induced liver cirrhosis and portal vein thrombosis had cadaveric liver transplantation, with the transplant reoriented in abdominal cavity 90° clockwise relative to the median plane. End-to-side cavocaval anastomosis was formed between the donor's retrohepatic and the recipient's main inferior vena cava, with successive portal and arterial anastomoses and complete donor liver reperfusion. A biliary reconstruction was performed with an end-to-end biliobiliary anastomosis. The surgery duration comprised 5 h 20 min, intraoperative blood loss — 2000 mL, cold ischemia time — 4 h. The patient was discharged on the 10th day after surgery in satisfactory condition.Conclusion. Situs inversus is not a contraindication to liver transplantation.